Gastrointestinal complications after cardiac surgery - Klara Schwarzova; Sameer Damle; Frank William Sellke; Michael Phillip Robich (Trauma Surgery & Acute Care Open)
Gastrointestinal complications after cardiac surgery are relatively rare entities but carry a high mortality. We identified over 70 articles written since 2010 using the PubMed database. We included 40 in our review. The most common complications include paralytic ileus, gastrointestinal bleeding, and bowel ischemia. Patients who undergo cardiac procedures are at risk for poor perfusion of the gastrointestinal tract and, thus, at risk for resulting complications. Risk factors for these complications include peri-operative use of vasopressors, prolonged operative time, and the time of cardiopulmonary bypass. Presentation of gastrointestinal complications tends to differ as patients after open heart surgery can remain intubated, and exams can be limited. Early recognition and aggressive therapy are paramount. We aim to provide a review that will help the reader get familiar with the most common gastrointestinal complications that can negatively affect outcomes after cardiac surgery.